Umwelt, KVP & DTD : Interactions entre Connaissances (K), Valeurs (V), Pratiques (P) & Délai de Transposition Didactique - Clément, Pierre (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2019)
Three concepts that structure my research in Didactics of Biology can also express convergence with the ATD. The umwelt: each living being constructs itself while constructing its world (its umwelt), in an eminently social context for human beings. KVP interactions between knowledge (K), values (V) and social practices (P): possible links with certain dimensions of the praxeological approach, but with more emphasis on values (V); Analysis of the different steps of didactic transposition; Comparison of the conceptions of teachers in thirty countries (notion of system of conceptions). The Didactic Transposition Delay (DTD) separates the emergence of new scientific knowledge from its insertion in programs, textbooks or in the teachers’ conceptions. Trois concepts qui structurent mes recherches en Didactique de la Biologie peuvent aussi exprimer des convergences avec la TAD. L’umwelt : chaque être vivant se construit tout en construisant son monde (son umwelt), dans un contexte éminemment social pour les humains. Les interactions KVP entre connaissances (K), valeurs (V) et pratiques sociales (P) : liens possibles avec certaines dimensions de l’approche praxéologique, mais en insistant plus sur les valeurs (V) ; analyse des différentes étapes de la transposition didactique ; comparaison des conceptions d’enseignants de trente pays. Le Délai de la Transposition Didactique (DTD) sépare l’émergence d’une nouvelle connaissance scientifique de son insertion dans les programmes, les manuels scolaires ou dans les conceptions des enseignants.